The trail of lost hearts - Garvis Graves, Tracey (St. Martin's Press, 2024)
"Thirty-four-year-old Wren Waters believes that if you pay attention, the universe will send you exactly what you need. But her worldview shatters when the universe delivers two life-altering blows she didn't see coming, and all she wants to do is put the whole heartbreaking mess behind her. No one is more surprised than Wren when she discovers that geocaching-the outdoor activity of using GPS to look for hidden objects-is the only thing getting her out of bed and out of her head. She decides that a weeklong solo quest geocaching in Oregon is exactly what she needs to take back control of her life. Enter Marshall Hendricks, a psychologist searching for distraction as he struggles with a life-altering blow of his own. Though Wren initially rebuffs Marshall's attempt at hiker small talk, she's beyond grateful when he rescues her from a horrifying encounter farther down the trail. In the interest of safety, Marshall suggests partnering up to look for additional caches. Wren's no longer quite so trusting of the universe-or men in general-but her inner circle might argue that a smart, charismatic psychologist isn't the worst thing the universe could place in her path. What begins as a platonic road trip gradually blossoms into something deeper, and the more Wren learns about Marshall, the more she wants to know. Now all she can do is hope that the universe gets it right this time"--